Bacteriology of urinary tract infection in pediatric patients at KIST Medical College Teaching Hospital - Raghubanshi, Birendra Raj; Shrestha, Devendra; Chaudhary, Mahesh; Karki, Bal Man Singh; Dhakal, Ajaya Kumar (Journal of Kathmandu Medical College, 2014)
Background: Urinary tract infection is common in children and is an important cause of morbidity. Urinary tract infection at young age can lead to renal injury and scarring, and ultimately lead to end stage renal disease in adulthood. Objectives: The purpose of study was to identify the different species of microorganisms, along with their antimicrobial susceptibility pattern, causing urinary tract infection in paediatric patients presenting with urinary tract infection at KIST Medical College, Imadol, Lalitpur, Nepal. Methods: This retrospective study examined microbiological and antimicrobial susceptibility pattern for urine samples collected at KIST Medical College, Imadol, Lalitpur from December 2010 to November 2013. A urine sample was included in our dataset if it demonstrated pure growth of a single organism and accompanying antimicrobial susceptibility and subject demographic data were available. Results: Escherichia coli was the most common organism isolated, followed by Klebsiella species, Staphylococcus species and then by Proteus species, Enterococcus species and Citrobacter species being equal in number. Microorganisms were most susceptible to amikacin and nitrofurantoin and most resistant to ampicillin and nalidixic acid. Conclusion: Though various microorganisms are responsible for urinary tract infection in children, Escherichia coli is the most common causative agent. Antimicrobial resistance has already emerged against many antibiotics, making empiric treatment of these infections challenging. DOI: http://dx.doi.org/10.3126/jkmc.v3i1.10919 Journal of Kathmandu Medical College Vol. 3, No. 1, Issue 7, Jan.-Mar., 2014, Page: 21-25